Testing for Clostridium difficile in Patients Newly Diagnosed with Inflammatory Bowel Disease in a Community Setting. Issue 3 (9th January 2015) - Krishnarao, Anita; de Leon, Lauren; Bright, Renee; Moniz, Heather; Law, Meaghan; Leleiko, Neal; Sands, Bruce E.; Merrick, Marjorie; Shapiro, Jason; Wallenstein, Sylvan; Giacalone, Julie; Shah, Samir A.
Abstract : Background: The incidence of Clostridium difficile infection (CDI) in inflammatory bowel disease (IBD) is increasing, and CDI has a negative impact on IBD outcomes with both increased morbidity and mortality. Data are lacking regarding the rate of appropriate testing for CDI at the time of diagnosis. Methods: We sought to determine the rate of CDI testing and CDI positivity at diagnosis of IBD using data collected through the Ocean State Crohn's and Colitis Area Registry (OSCCAR), a prospective cohort of patients with newly diagnosed IBD. CDI testing and CDI positivity were determined by reviewing the medical records of patients enrolled into the registry and diagnosed with IBD between January 2008 and July 2011. Results: Of 320 enrolled patients, 227 (70.9%) reported diarrhea, and CDI testing was performed for 113 (49.8%) of the 227 patients. CDI testing was not recorded as being performed for the remaining 114 patients who reported having diarrhea. An additional 24 patients were tested for CDI but did not report having diarrhea. Seven (5.1%) of the 137 patients tested for CDI were positive. Conclusions: Testing for CDI is significantly lower than expected at diagnosis of IBD. Although the prevalence of CDI among tested patients is approximately 5%, a low testing rate suggests a significant quality issue in the diagnosis of IBD, with the potential for delayed diagnosis of CDI.